Karakter Kepemimpinan Transformasional Petrus Octavianus Sebagai Pendidik Kristen - Yakobus Adi Saingo (Jurnal Shanan, 2023)
The purpose of this research is to provide a pedagogical understanding of Petrus Octavianus in terms of his transformational leadership character as a successful Christian education missionary, including being able to establish a theology-based Christian educational institution, namely the Indonesian Bible Institute (I-3) in Batu City, East Java which is very useful for equip God's servants in terms of character building, spirituality, and increasing human resource competence. This research uses a qualitative method with a narrative-descriptive model through the process of collecting data through a literature study approach, in which the researcher collects various information from relevant literature and is related to the theme of the discussion and then reduces it to describe the research subject, namely Petrus Octavianus. The results of the study suggest that the transformational leadership character of Petrus Octavianus as a Christian education missionary includes upholding aspects of spirituality, acting progressively, visionary, open-mindedness, adaptability, exemplary humility, innovative, charismatic, warrior spirit, ability to influence, integrity and the ability to create new leaders in the course of his ministry mission. The typical transformational leadership character of Pastor Petrus Octavianus is as a leader capable of bringing about change in the world of Christian education and ecclesiastical ministry and inspiring many of God's servants to put aside personal interests for the good of the organization.